CK14 Expression Identifies a Basal/Squamous-Like Type of Papillary Non-Muscle-Invasive Upper Tract Urothelial Carcinoma - Jung, Minsun; Jang, Insoon; Kim, Kwangsoo; Moon, Kyung Chul (Frontiers in Oncology, 2020)
Object: CK14 expression is an important marker of basal/squamous-like (BASQ)-type muscle-invasive bladder carcinoma, and this molecularly defined subtype has a poor prognosis and a distinct response to chemotherapy. However, CK14 expression and its clinicopathological and molecular significance in papillary non-muscle-invasive upper tract urothelial carcinoma (NMIUTUC) remain unknown. Herein, we investigated the prognostic implications of immunohistochemical (IHC) staining for CK14 and the transcriptional characteristics associated with CK14 expression in papillary NMIUTUC. Materials and methods: IHC staining for CK14 was conducted in 204 papillary NMIUTUC specimens. Positive CK14 IHC staining was defined as a positive signal in >0% of tumor cells. RNA sequencing data were analyzed from 8 papillary high-grade NMIUTUC specimens consisting of 4 CK14-positive and 4 CK14-negative tumors. Results: CK14 positivity was associated with a high TNM stage (p <0.001) and a high World Health Organization grade (p = 0.003). Survival analysis showed that CK14 positivity was significantly associated with poor progression-free survival (p = 0.015; hazard ratio [HR] = 2.990; 95% confidence interval [CI] = 1.180-7.580) and was marginally associated with poor cancer-specific survival (p = 0.052; HR = 3.77; 95% CI = 0.900-15.780). Gene set enrichment analysis demonstrated that the CK14-positive tumors were associated with a basal subtype of breast cancer, squamous cell carcinoma development, p40, tumor necrosis factor α-nuclear factor-κB, and p53 pathways, and embryonic stem cells; these characteristics are reminiscent of the BASQ subtype. In addition, with a p-value <0.05 and |fold change| ≥2 as the cutoffs, we identified 178 differentially expressed genes when comparing CK14-positive and CK14-negative tumors. Functional analysis of these genes revealed several networks and gene ontology terms related to the positive regulation of cellular proliferation in CK14-positive tumors. Consistent with these results, we demonstrated that the mean Ki-67 proliferative index was higher in CK14-positive tumors than it was in CK14-negative tumors (2.3% vs. 0.8%, respectively, p = 0.002). Conclusion: CK14-positive papillary NMIUTUC is an aggressive subtype with BASQ-like molecular characteristics and dynamic proliferative activity. We propose that CK14 IHC staining can be a useful biomarker of BASQ-type papillary NMIUTUC that can be applied in daily practice with the aim of precision oncology.